Πειραματικός υπολογισμός γεωθερμικών παραμέτρων - Ποντικού, Εύρος (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2012)
Thermal properties of soil are important for the design of a geothermal heat exchanger. The most essential properties are the thermal conductivity (λ), the specific heat of soil (c), density (ρ) and thermal diffusivity of the ground (a).These properties are calculated with experimental measurements.The results of the experimental measurements are analysed using various mathematical relationships.These relationships describe the heat transfer in thermal equilibrium between the ground and the fluid in the heat exchanger.A barrel measuring 65 cm in diameter and 120 cm in height has been placed at the workshops of the Mechanical Engineering Department.Three parallel vertical U heat exchangers, made of copper and sand were installed in the barrel.Thermocouples were fitted along the length of the vertical heat exchangers at various distances (23 cm, 34 cm, 57 cm).The empty place in the barrel was covered with the base layer and three more layers: (a) red coloured soil (23 cm) (b) mixture of red coloured soil, bentonite and sand (23 cm) and (c) mixture of bentonite and sand (24 cm).The thermal conductivity and density were measured for each layer.The experiment was based on the recirculation of water with a constant velocity flow through three pumps.Four resistors arranged in parallel (of 18 Ohm each) were used for each pump in order to operate at the required speed.The water which was re-circulated in the main heat exchanger was heated continuously with an electric heating element (coil) of 18.95 W, 12 W, 9.45 W power, mounted in a specially designed and insulated container. Constant voltage was supplied to the heating element by a transformer connected to the EAC network.The water which was re-circulated in the other two heat exchangers which were peripherally mounted, was placed in specially designed and insulated containers.Three thermistors which were connected to temperature recording devices were used to record the temperature of the water in the containers.Thermal conductivity and volumetric specific heat capacity were calculated by using the methods of line source and the rate of temperature fall after the delivery of a heat pulse in three experiments.The experimental thermal conductivities measurements using the line source method were λ1 = 1.84 W/m.K, λ2 = 0.719 W/m.K, λ3 = 0.750 W/m.K.The same measurements using the second method were λ1 = 2.306 W/m.K, λ2 = 0.294 W/m.K, λ3 = 0.361 W/m.K.The specific volumetric heat capacity at a distance of 0.08 m was C1=12001666.67 J/m3K, C2=14972343.75 J/m3K, C3=826478.8732 J/m3K while at a distance 0.2 m was C1=3661525.424 J/ m3K, C2=2921432.927 J/m3K , C3=199591.8367 J/m3K respectively. The theoretical value of thermal conductivity was λ = 0.316 W/m.K and the specific volumetric heat capacity was C=145700000 J/m3K.
Keywords: Geothermal heat exchanger; Γεωθερμικός εναλλακτής